Surgical treatment results cervical esophageal cancer - Henderson, Eduardo (Cirugía del Uruguay, 1994)
A bibliographical review of the results of surgical treatment of cancer of the surgical esophague is presented by means of an anatomical summary, epidemiology and diagnosis; different therapeutical options are a/so presented as we/1 as an analysis of results in a reference center such as the Service of Digestive Surgery at Beaujon Hospital in París, France.